Validation of the Montreal cognitive assessment versus mini-mental state examination against hypertension and hypertensive arteriopathy after transient ischemic attack or minor stroke. - Webb, A; Pendlebury, S; Li, L; Simoni, M; Lovett, N; Mehta, Z; Rothwell, P (Lippincott Williams and Wilkins, 2014)
BACKGROUND AND PURPOSE: Lack of reduced cognitive impairment with blood pressure (BP) lowering in trials may reflect use of the Mini-Mental State Examination (MMSE), which is insensitive to mild cognitive impairment after cerebrovascular events compared with the Montreal Cognitive Assessment. We determined relationships between impairment on MMSE versus Montreal Cognitive Assessment (MoCA) with the major physiological determinant of vascular cognitive impairment: hypertension and hypertensive arteriopathy. METHODS: Cognitive impairment in consecutive patients 6 months after transient ischemic attack or minor stroke was defined as significant, mild, or none (MMSE<23, 23-26, ≥27; MoCA<20, 20-24, ≥25) and related to 20 premorbid systolic BP readings, home BP measurement (3 measurements, 3×daily for 1 month), and hypertensive arteriopathy (creatinine, stroke versus transient ischemic attack, leukoaraiosis) by ordinal regression. RESULTS: Of 463 patients, 45% versus 28% had at least mild cognitive impairment on the MoCA versus MMSE (P<0.001). Hypertensive arteriopathy was more strongly associated with cognitive impairment on the MoCA than MMSE (creatinine: odds ratio=3.99; 95% confidence interval, 2.06-7.73 versus 2.16, 1.08-4.33; event: 1.53, 1.06-2.19 versus 1.23, 0.81-1.85; leukoaraiosis: 2.09, 1.42-3.06 versus 1.34, 0.87-2.07). Premorbid and home BP measurement systolic BP were more strongly associated with impairment on vascular subdomains of the MoCA than MMSE (odds ratio/10 mm Hg: visuospatial 1.29 versus 1.05; attention 1.18 versus 1.07; language 1.22 versus 0.91; naming 1.07 versus 0.86). CONCLUSIONS: The stronger relationship between impairment on the MoCA with hypertensive arteriopathy, independent of age, indicates a greater sensitivity for vascular-origin cognitive impairment. Use of MoCA should improve sensitivity for cognitive impairment and treatment effects in future studies.